Talk or Text? : Evaluating Response Rates by Remote Survey Method during COVID-19 - Amaral, Sofia; Dinarte Diaz, Lelys; Dominguez, Patricio; Perez-Vincent, Santiago M.; Romero, Steffanny (World Bank, Washington, DC, 2022)
Researchers and policy makers face significant challenges in selecting a method to conduct remote surveys, especially when collecting sensitive information or during turbulent life stages of hard-to-reach groups. In the context of the COVID-19 lockdown, this study randomly selected about 600 adults in El Salvador to survey using two different tools: telephone interviews or a self-completion survey via WhatsApp. The findings show that phone-based surveys increase the rate of survey completion by 42 percentage points. Even larger effects are documented for women and older adults. Although the direct costs of phone-based surveys are substantially higher—doubling implementation cost—the estimates imply that when adjusted for the probability of completion, the costs of conducting phone-based surveys can be 25 percent lower.